Biocontrol potential of Trichoderma harzianum isolate T-aloe against Sclerotinia sclerotiorum in soybean - Zhang, Fuli; Ge, Honglian; Zhang, Fan; Guo, Ning; Wang, Yucheng; Chen, Long; Ji, Xiue; Li, Chengwei (Plant physiology and biochemistry, 2016)
Sclerotinia stem rot, caused by Sclerotinia sclerotiorum (Lib.) de Bary is a major disease of soybean (Glycine max (L.) Merr.). At present, we revealed the three-way interaction between Trichoderma harzianum T-aloe, pathogen S. sclerotiorum and soybean plants in order to demonstrate biocontrol mechanism and evaluate biocontrol potential of T-aloe against S. sclerotiorum in soybean. In our experiments, T-aloe inhibited the growth of S. sclerotiorum with an efficiency of 56.3% in dual culture tests. T-aloe hyphae grew in parallel or intertwined with S. sclerotiorum hyphae and produced hooked contact branches, indicating mycoparasitism. Plate tests showed that T-aloe culture filtrate inhibited S. sclerotiorum growth with an inhibition efficiency of 51.2% and sclerotia production. T-aloe pretreatment showed growth-promoting effect on soybean plants. The activities of peroxidase, superoxide dismutase, and catalase increased, and the hydrogen peroxide (H2O2) as well as the superoxide radical (O2-) content in soybean leaves decreased after T-aloe pretreatment in response to S. sclerotiorum pathogen challenge. T-aloe treatment diminished damage caused by pathogen stress on soybean leaf cell membrane, and increased chlorophyll as well as total phenol contents. The defense-related genes PR1, PR2, and PR3 were expressed in the leaves of T-aloe-treated plants. In summary, T-aloe displayed biocontrol potential against S. sclerotiorum. This is the first report of unraveling biocontrol potential of Trichoderma Spp. to soybean sclerotinia stem rot from the three-way interaction between the biocontrol agent, pathogen S. sclerotiorum and soybean plants. •Trichoderma harzianum T-aloe showed growth-promoting effect on soybean seedlings.•T-aloe showed biocontrol potential against Sclerotinia sclerotiorum in soybean.•T-aloe treatment diminished ROS damage and induced defense-related genes expression.